(untitled) (JURNAL KEPERAWATAN, 2014)
Abstract :KIA’S book is a book containing the records of maternal and child health as well as a wide range of information on how to maintain and care for maternal and child health. This book is available in health care facilities such as clinics and hospitals. Research objectives: to know the relationship of knowledge and attitudes about antenatal care of pregnant women with the use of the books in the region Seek KIA Ranotana Weru Kec. Wanea Manado. Design research: Observational analytic with cross sectional approach. This research was conducted in clinics Ranotana Weru on 24 July-20 August 2014. Sample: in this research is purposive sampling with 63 respondents who meet the criteria of inclusion. Research instrument that uses a questionnaire. Statistical test: using a computerized system by using the chi-square test (XÂ²) at the 95% significance level (Ã¡ = 0.05%). Results: the results obtained by the p-value = 0.025 to the level of significance < 0.05. This shows there is a meaningful relationship between Knowledge by the use of book KIA, and obtained also results p-value = 1,000 the level of significance > 0,05. This shows no relation attitude to the use of book KIA. Conclusion: the higher level knowledge pregnant mothers the more good also use book KIA for pregnant women. Keywords : knowledge, attitude, use of Book KIA Abstrak : Buku KIA adalah buku yang berisi catatan kesehatan ibu dan anak serta berbagai informasi cara memelihara dan merawat kesehatan ibu dan anak. Buku ini tersedia di fasilitas pelayanan kesehatan seperti puskesmas dan rumah sakit. Tujuan Penelitian: untuk mengetahui hubungan pengetahuan dan sikap ibu hamil tentang antenatal care dengan penggunaan buku KIA di Wilayah Kerja Puskesmas Ranotana Weru Kec. Wanea Manado.Desain Penelitian:Observasional analitik dengan pendekatan cross sectional. Penelitian ini dilakukan di puskesmas Ranotana Weru pada 24 juli-20 agustus 2014.Sampel: dalam penelitian ini adalah purposive sampling dengan 63 responden yang memenuhi kriteria inklusi. Instrumen penelitian yaitu menggunakan kuesioner.Uji statistik:menggunakan sistem komputerisasi dengan menggunakan uji chisquare ( ) pada tingkat kemaknaan 95% (Ã¡ = 0,05). Hasil: diperoleh hasil p-value = 0,025 dengan level of significance< 0,05. Ini menunjukkan ada hubungan bermakna antara pengetahuan dengan penggunaan buku KIA, dan diperoleh juga hasil p-value = 1,000 dengan level of significance> 0,05. Ini menunjukkan tidak ada hubungan sikap dengan penggunaan buku KIA. Kesimpulan: semakin tinggi tingkat pengetahuan ibu hamil maka semakin baik juga penggunaan buku KIA pada ibu hamil. Kata Kunci : Pengetahuan, Sikap, Penggunaan Buku KIA